Identification of zinc finger protein of the cerebellum 5 as a survival factor of prostate and colorectal cancer cells. Issue 12 (25th October 2017) - Satow, Reiko; Inagaki, Shota; Kato, Chiaki; Shimozawa, Makoto; Fukami, Kiyoko
Abstract : Identification of specific drug targets is very important for cancer therapy. We recently identified zinc finger protein of the cerebellum 5 (ZIC5) as a factor that promotes melanoma aggressiveness by platelet‐derived growth factor D (PDGFD) expression. However, its roles in other cancer types remain largely unknown. Here we determined the roles of ZIC5 in prostate cancer (PCa) and colorectal cancer (CRC) cells. Results showed that ZIC5 was highly expressed in CRC and dedifferentiated PCa tissues, whereas little expression was observed in relevant normal tissues. Knockdown of ZIC5 decreased proliferation of several PCa and CRC cell lines with induction of cell death. ZIC5 knockdown significantly suppressed PDGFD expression transcriptionally, and PDGFD suppression also decreased proliferation of PCa and CRC cell lines. In addition, suppression of ZIC5 or PDGFD expression decreased levels of phosphorylated focal adhesion kinase (FAK) and signal transducer and activator of transcription 3 (STAT3) which are associated with PCa and CRC aggressiveness. Furthermore, knockdown of ZIC5 or PDGFD enhanced death of PCa and CRC cells induced by the anti‐cancer drugs docetaxel or oxaliplatin, respectively. These results suggest that ZIC5 and PDGFD promote survival of PCa and CRC cells by enhancing FAK and STAT3 activity, and that the roles of ZIC5 are consistent across several cancer types. Abstract : ZIC5 is highly expressed in prostate and colorectal cancer tissues, and its suppression abrogates cell proliferation, migration, and survival. Notably, suppression of ZIC5 and its downstream factor, PDGFD, enhanced prostate and colorectal cancer cell death induced by anti‐cancer drugs.